1995
DOI: 10.1111/j.1442-2042.1995.tb00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Occurrence of Urothelial Tumors in Dye Workers Exposed to Aromatic Mines

Abstract: 1) The manufacturing and handling of benzidine and duration of exposure contribute significantly to the occurrence of occupational urothelial tumor, the former more strongly than the latter; 2) the contribution of different job types to tumor occurrence may be dependent upon the industrial health and safety practices in each factory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 3 publications
0
18
0
2
Order By: Relevance
“…[41][42][43][44] Second, exposure to benzidine and other arylamines has been associated with increased risks of bladder cancer in both Asian and Caucasian workers. 17,[45][46][47][48][49][50] Third, as shown in the metaanalysis presented in Table III of Asian populations not exposed to arylamines in the workplace, studies have shown that slow acetylation is a risk factor for bladder cancer comparable to the risk found in Caucasian populations, and the magnitude of the relative risk is the same. 3 Fourth, even though racial differences in the allele distribution among different ethnic groups have been reported, almost all of the alleles found in Caucasian groups have been described in Asian populations.…”
Section: Discussionmentioning
confidence: 93%
“…[41][42][43][44] Second, exposure to benzidine and other arylamines has been associated with increased risks of bladder cancer in both Asian and Caucasian workers. 17,[45][46][47][48][49][50] Third, as shown in the metaanalysis presented in Table III of Asian populations not exposed to arylamines in the workplace, studies have shown that slow acetylation is a risk factor for bladder cancer comparable to the risk found in Caucasian populations, and the magnitude of the relative risk is the same. 3 Fourth, even though racial differences in the allele distribution among different ethnic groups have been reported, almost all of the alleles found in Caucasian groups have been described in Asian populations.…”
Section: Discussionmentioning
confidence: 93%
“…These aromatic hydrocarbons have been and are used in many industries (dyes, textiles, rubber, chemicals, petrochemicals, coal) and research. Aromatic amines are responsible for the carcinogenicity of certain chemicals, including benzidine and β‐naphtylanine [1,11]. These two pathogens have been phased out since 1960 and were eventually banned in most industrialized countries.…”
Section: Occupation‐related Uut‐uccmentioning
confidence: 99%
“…The estimated risk (OR) of developing TCC when exposed to aromatic amines is 8.3 according to Shinka et al . [11].…”
Section: Occupation‐related Uut‐uccmentioning
confidence: 99%
“…On the other hand, UTUCs are relatively uncommon and account for only 5 to 10 % of all urothelial carcinomas [3]. The etiology of all UCs, from both anatomical locations, share common carcinogens, including tobacco and aromatic amines, such as benzidine and β-naphtylanine [4][5][6]. It is true that some contributory factors, however, show a stronger impact on UTUC than on UBUC; for example, patients with endemic Balkans nephropathy [7,8], Chinese herb nephropathy [8,9], and analgesic nephropathy [10] are more susceptible to UTUC than UBUC.…”
Section: Introductionmentioning
confidence: 99%